2017
DOI: 10.1101/119446
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Coexistence in Species with Continuous Ontogenetic Niche Shifts and Competitive Asymmetry

Abstract: A longstanding problem in ecology is whether structured life cycles impede or facilitate coexistence between species. Theory based on populations with two discrete stages in the life-cycle indicates that coexistence requires at least one species to shift its niche between stages and that each species is a better competitor in one of the niches. However, in many cases, niche shifts are associated with changes in an underlying continuous trait like organism size and we have few predictions for how the conditions… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(32 citation statements)
references
References 57 publications
0
32
0
Order By: Relevance
“…Werner & Hall, 1988). For organisms with distinct life stages, such as aquatic insects and amphibians, these shifts are typically abrupt and consist of complete switches between separate niches following metamorphosis (Claessen & Dieckmann, 2002;Bassar, Travis & Coulson, 2017). Most organisms, however, exhibit less-abrupt shifts in niche utilisation, but ODSs may nonetheless manifest as relatively distinct changes in prey choice or diet composition associated with shifts in habitat use during ontogeny, as is often seen in fish (Fig.…”
Section: The Nature Of Odssmentioning
confidence: 99%
“…Werner & Hall, 1988). For organisms with distinct life stages, such as aquatic insects and amphibians, these shifts are typically abrupt and consist of complete switches between separate niches following metamorphosis (Claessen & Dieckmann, 2002;Bassar, Travis & Coulson, 2017). Most organisms, however, exhibit less-abrupt shifts in niche utilisation, but ODSs may nonetheless manifest as relatively distinct changes in prey choice or diet composition associated with shifts in habitat use during ontogeny, as is often seen in fish (Fig.…”
Section: The Nature Of Odssmentioning
confidence: 99%
“…In more complicated models, interaction coefficients can be replaced with functions, and the population size of interacting species replaced with information on population structure (Inouye 2001, McCoy and Bolker 2008, Bassar et al 2017. Such formulations are useful as empirical observations have revealed that the outcomes of interactions between two individuals are often dependent upon their phenotypic trait values (Bolnick et al 2011).…”
Section: Resources Species Interactions and Trophic Cascadesmentioning
confidence: 99%
“…When individual specialisation is determined by phenotypic traits, this can result in competitive interactions between individuals varying as a function of the distance between their trait values. Such trait-mediated interactions either within or between speciescan have significant impacts on the diversity of resources that are utilised by a species, patterns of resource use, community dynamics, selection, and evolution (Roughgarden 1972, Bassar et al 2017.…”
Section: Resources Species Interactions and Trophic Cascadesmentioning
confidence: 99%
See 2 more Smart Citations